2013
DOI: 10.1161/hypertensionaha.113.01319
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension After Preeclampsia Is Preceded by Changes in Cardiac Structure and Function

Abstract: P reeclampsia (PE), a serious hypertensive pregnancy disorder complicating 2% to 5% of all pregnancies, is characterized by new-onset hypertension along with de novo proteinuria after 20 weeks of gestation 1 or new-onset proteinuria that develops after 20 weeks in women with preexisting hypertension. Women with a history of PE have an increased risk to develop chronic hypertension and related cardiovascular morbidity and mortality. 2 PE is accompanied by concentric left ventricular remodeling along with diasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
52
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 31 publications
9
52
2
1
Order By: Relevance
“…16 Adding the excluded women who remained hypertensive after the preeclamptic index pregnancy (47/386; 12%)) the overall prevalence of hypertension after preeclampsia is comparable with the mean prevalence of 30% to 40% found in other studies in formerly preeclampsia women. 6,[17][18][19][20] Our data show that a substantial proportion of women progressed within a few years from normotension to hypertension.…”
Section: Discussionmentioning
confidence: 55%
“…16 Adding the excluded women who remained hypertensive after the preeclamptic index pregnancy (47/386; 12%)) the overall prevalence of hypertension after preeclampsia is comparable with the mean prevalence of 30% to 40% found in other studies in formerly preeclampsia women. 6,[17][18][19][20] Our data show that a substantial proportion of women progressed within a few years from normotension to hypertension.…”
Section: Discussionmentioning
confidence: 55%
“…Solanki et al [4] and Ghossein Doha et al [5] studied the same parameter in pre-eclamptics and normotensives and found a significant difference in LVEDV between the two groups (108.23 ± 27.95 vs. 107.73 ± 5.66 ml, 100 ± 16 vs. 94 ± 7 ml).…”
Section: Discussionmentioning
confidence: 96%
“…Ghossein Doha et al [5] studied systolic parameters in 40 pre-eclamptic women and 40 normotensive women and concluded that the mean LVEDV was higher in preeclamptic group, i.e. (100 ± 16 vs. 94 ± 7 ml), highlighting the importance of this variable in early detection of cardiovascular morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…6 Increased preload, in conjunction with the decreased peripheral resistance, leads to an increase in cardiac output. These physiologic changes lead to left ventricular remodeling and mild left ventricular hypertrophy.…”
Section: Echocardiographymentioning
confidence: 99%
“…Pregnant women with preeclampsia and multiple gestation exhibit additional increase in left ventricular mass. 6 Regional wall motion abnormalities (RWMA) are not seen in normal pregnancy, and if observed, indicate myocardial ischemia or injury. 7 This finding is especially helpful in the setting of equivocal ECG changes, when RWMA not only serves as diagnostic guides, but also as prognostic indicators for further cardiac events.…”
Section: Echocardiographymentioning
confidence: 99%